Sport and Physical Activities as the Ground for Supporting Subjective Well-being - Elaheh Medadi Nansa; Farzad Ghafouri (New Approaches in Sport Sciences)
There is almost a global consensus over this fact that well-being is the ultimate purpose of any policy-making, especially in democratic governments. Participating in organized sports is regarded as one of the important social grounds (institutions) with the potential capability of supporting the mental health. High and long-term participation and attractive environments make organized sports a significant and positive instrument for facilitating the population level change in case of health treatments such as promoting the mental health, enhancing the emotional/social performance and the life quality related to social relationships. Taking part in sports spaces and fields or watching the sport matches create this feeling in the individuals that there is something going on that is far more important than the scores and results; as if the collective mind is given a new energy, and the individuals experience a sort of joy and happiness caused by participating in sport events or just watching them. Sports can be an attractive environment for supporting the subjective well-being, which can be realized by focusing on the importance of sports in childhood and adolescence, while supporting the subjective well-being in such periods and considering its positive effects on the future periods of life. Since subjective well-being is considered as a developmental index of societies and regarding the significant role of sports and physical activities in creating such feeling, it seems necessary that more attention be paid to sports and principled investments be done in this social institution, besides having responsible management and planning. The instances of such marks can be enumerated as the development of sport clubs, development of sport for all, building health roadin public places like parks and sidewalks, and providing sports and sports facilities for all categories and groups of the society regardless of gender, age and ethnicity.